Biological foundations of optimization of training loads of athletes - Shan, M.; Kozhedub, M. S.; Vrublevskiy, E. P. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to consisted in studying the main approaches of the coaches of Belarus and China to taking into account the biorhythmological characteristics of the athletes' body when planning their training process and determining the dynamics of the manifestation of speed and strength abilities during the OMC among athletes specializing in various sports.